Towards Establishing Best Practice in the Analysis of Hydrogen and Deuterium by Atom Probe Tomography - Gault, Baptiste; Saksena, Aparna; Sauvage, Xavier; Bagot, Paul; Aota, Leonardo S; Arlt, Jonas; Belkacemi, Lisa T; Boll, Torben; Chen, Yi-Sheng; Daly, Luke; Djukic, Milos B; Douglas, James O; et al. (Microscopy and microanalysis, 2024)
As hydrogen is touted as a key player in the decarbonization of modern society, it is critical to enable quantitative hydrogen (H) analysis at high spatial resolution and, if possible, at the atomic scale. H has a known deleterious impact on the mechanical properties (strength, ductility, toughness) of most materials that can hinder their use as part of the infrastructure of a hydrogen-based economy. Enabling H mapping including local hydrogen concentration analyses at specific microstructural features is essential for understanding the multiple ways that H affect the properties of materials including embrittlement mechanisms and their synergies. In addition, spatial mapping and quantification of hydrogen isotopes is essential to accurately predict tritium inventory of future fusion power plants thus ensuring their safe and efficient operation. Atom probe tomography (APT) has the intrinsic capability to detect H and deuterium (D), and in principle the capacity for performing quantitative mapping of H within a material's microstructure. Yet, the accuracy and precision of H analysis by APT remain affected by complex field evaporation behavior and the influence of residual hydrogen from the ultrahigh vacuum chamber that can obscure the signal of H from within the material. The present article reports a summary of discussions at a focused workshop held at the Max-Planck Institute for Sustainable Materials in April 2024. The workshop was organized to pave the way to establishing best practices in reporting APT data for the analysis of H. We first summarize the key aspects of the intricacies of H analysis by APT and then propose a path for better reporting of the relevant data to support interpretation of APT-based H analysis in materials.